SEX DIFFERENCES IN SKELETAL MUSCLE ENERGETICS AMONG OLDER ADULTS. (20th December 2022) - Kramer, Philip; Distefano, Giovanna; Ramos, Sofhia; Goodpaster, Bret; Coen, Paul; Marcinek, David; Cawthon, Peggy; Molina, Anthony
Abstract: Mobility impairment is the most common disability among older adults, with an earlier presentation, higher prevalence, and greater severity in women compared to men. A decline in skeletal muscle metabolism contributes to the loss of mobility with age. However, it is unknown if sex-specific differences in muscle energetics can explain the disparity in mobility impairment among men and women. In the Study of Muscle, Mobility, and Aging (SOMMA), muscle energetics was characterized using in vivo Phosphorus Magnetic Resonance Spectroscopy and High-Resolution Respirometry of permeabilized fiber bundles from muscle biopsies. In this analysis of 773 participants aged 70–94 years, 519 were women, of which 16% were deemed lower extremity mobility impaired based on a Short Physical Performance Battery (SPPB) score